P236 Is the association of physical activity with FEV1 and FVC partially mediated by C-reactive protein levels?: The ECRHS study. (December 2018) - Fuertes, E; Carsin, AE; Garcia-Larsen, V; Guerra, S; Pin, I; Leynaert, B; Accordini, S; Martinez-Moratalla, J; Anto, JM; Urrutia, I; Le Gouellec, A; Heinrich, J; et al.
Abstract : Introduction and objective: We have shown that regular physical activity is associated with higher lung function, particularly in smokers, in a large multicenter adult cohort (the European Community Respiratory Health Survey, ECRHS 1 ). One possible mechanism for this association is that physical activity reduces systemic inflammation. Here, we tested whether C-reactive protein (CRP), a marker of systemic inflammation, is a mediator in the association of physical activity with forced expiratory volume in one second (FEV1) and forced vital capacity (FVC). Methods: Physical activity was assessed by self-report of being physically active (≥2 times and ≥1 hour per week of vigorous physical activity). A subsample was assessed 10 years later using the International Physical Activity Questionnaire (activity considered in tertiles of Metabolic Equivalent of Task (METs)-min per week in moderate physical activity). All participants had spirometry and CRP levels assessed, the latter of which followed a log normal distribution. Cross-sectional mixed linear regression models (adjusted for age, sex, height, education, occupation, secondhand smoke exposure, smoking status and center) were constructed, and the evidence supporting CRP as a mediator assessed using the 'mediate' package in the program 'R'. Results: Data on vigorous physical activity and CRP were available for 2347 adults (28–56 years-old). The subsample with physical activity data also measured in METs (assessed ten years later) was smaller (n=671, 40–67 years-old). Despite positive significant associations between nearly all physical activity metrics with FEV1 and FVC, there was no evidence that this was mediated through changing CRP levels (figure 1). A mediation effect by CRP was only apparent in the smaller subsample when comparing the second to first tertiles of METs in moderate activity (mean difference [95% CIs]: 21.1 ml [5.2, 41.9] for FEV1 and 17.3 ml [2.6, 38.0] for FVC). Conclusions: We found no consistent evidence that CRP mediates the association of physical activity with FEV1 or FVC. Future studies should evaluate other biomarkers of systemic inflammation and include more detailed and repeated data on physical activity and important covariates. References: Fuertes E et al . Leisure-time vigorous physical activity is associated with better lung function: The prospective ECRHS study. Thorax 2018;thoraxjnl-2017.